Genetic Relationship of Sago Palm (Metroxylon sagu Rottb.) in Indonesia Based on RAPD Markers - BARAHIMA ABBAS; MUHAMMAD HASIM BINTORO; SUDARSONO SUDARSONO; MEMEN SURAHMAN; HIROSHI EHARA (Society for Indonesian Biodiversity, 2009)
The areas of sago palm (Metroxylon sagu Rottb.) forest and cultivation in the world were estimated two million hectares andpredicted 50% of that areas located in Indonesia. Distribution of sago palm areas in Indonesia is not evenly distributed as well as their diversities. Information of plant genetic diversities and genetic relationship is very important to be used for germplasm collection and conservation. The objectives of research were revealed the genetic relationships of sago palm in Indonesia based on RAPD molecular markers. Fragments amplification PCR products were separated on 1.7% agarose gel, fixation in Ethidium Bromide, and visualized by using Densitograph. Genetic relationships of sago palm in Indonesia showed that sample in individual level were inclined mixed among the other and just formed three groups. Genetic relationship of sago palm population showed that samples populations from Jayapura, Serui, Sorong, Pontianak, and Selat Panjang were closely related each others based on phylogenetic analysis and formed clustered in one group, event though inclined to be formed two subgroups. Populations from Manokwari, Bogor, Ambon and Palopo were closed related each others, they were in one group. Genetic relationships in the level of island were showed sago palm from Papua, Kalimantan, and Sumatra closely related. Sago palms from Maluku were closed related with sago palm from Sulawesi whereas sago palm from Java separated from the others. Based on this observation we proposed that Papua as centre of sago palm diversities and the origin of sago palm in Indonesia. This research informed us the best way to decide sago palm places for germplasm of sago palm conservation activity.Key words: genetic relationships, population, sago palm, RAPD, Indonesia